2020
DOI: 10.1371/journal.pone.0243199
|View full text |Cite
|
Sign up to set email alerts
|

Joint influences of obesity, diabetes, and hypertension on indices of ventricular remodeling: Findings from the community-based Framingham Heart Study

Abstract: Introduction Obesity, hypertension, and diabetes are independently associated with cardiac remodeling and frequently co-cluster. The conjoint and separate influences of these conditions on cardiac remodeling have not been investigated. Materials and methods We evaluated 5,741 Framingham Study participants (mean age 50 years, 55% women) who underwent echocardiographic measurements of left ventricular (LV) mass (LVM), LV ejection fraction (LVEF), global longitudinal strain (GLS), mitral E/e’, left atrial end-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 60 publications
3
16
0
9
Order By: Relevance
“…Consistent with a recent study in older people, 11) our study revealed that both RASM and grip strength were positively associated with LVM, but the association disappeared after the adjustment for the age, sex, BMI, WHR, smoking, drinking, history of hypertension, and T2DM, implying that the association may have been overwhelmed by other risk factors of higher LVM, such as obesity, hypertension, and T2DM. 18,19) Moreover, we found that left ventricular diastolic function demonstrated age-dependent decline, consistent with previous studies. 17,20) Left ventricular diastolic dysfunction characterized as a filling impairment of the left ventricle is regarded as a predictor of the development of HF.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with a recent study in older people, 11) our study revealed that both RASM and grip strength were positively associated with LVM, but the association disappeared after the adjustment for the age, sex, BMI, WHR, smoking, drinking, history of hypertension, and T2DM, implying that the association may have been overwhelmed by other risk factors of higher LVM, such as obesity, hypertension, and T2DM. 18,19) Moreover, we found that left ventricular diastolic function demonstrated age-dependent decline, consistent with previous studies. 17,20) Left ventricular diastolic dysfunction characterized as a filling impairment of the left ventricle is regarded as a predictor of the development of HF.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, research based on the Framingham Heart Study has revealed the significant conjoint associations of hypertension and diabetes with GLS, suggesting a synergistic effects on the reduced GLS. 22 Ballo et al demonstrated that diabetes, but not hypertension, exerted a negative effect on LV systolic function. 23 The current study revealed that T2DM patients with reduced GLS preferentially suffered higher systolic blood pressure, compared with those with GLS ≥18%, further validating the adverse influence of hypertension on the subclinical myocardial injury.…”
Section: Clinical Risk Factors and LV Longitudinal Myocardial Functionmentioning
confidence: 99%
“…Jau Framingham tyrimo metu buvo nustatyta, kad sergantieji CD dažniau sirgo ŠKL, nei tie, kurie nesirgo CD. Tyrėjai to negalėjo paaiškinti įprastiniais rizikos veiksniais, o ypač didelio moterų, sirgusių CD, sergamumo ir mirtingumo, nebūdingo tipiškam ŠKL pasireiškimui [5]. Aterosklerozinė ŠKL sergantiesiems 2 tipo CD vidutiniškai pasireiškia 14,6 metų anksčiau ir pasireiškimas yra sunkesnis, nei pacientams, neturintiems hiperglikemijos [4].…”
Section: įVadasunclassified